Preservation of Natural Colorant Extract of Jalawe Fruit Peel (Terminalia bellirica) in Water-Based Solution - Edia Rahayuningsih; Ayub Wijayanto; Putri Nurfitasari (Indonesian Journal of Chemistry, 2016)
The general objective of this study is to preserve natural colorant extract of jalawe fruit peel in water-based solution during storing. The specific objectives in this research are finding suitable type and amount of antimicrobial compound to prevent biological degradation of the natural colorant jalawe extract, as well as determining the colorant half-life by evaluating its degradation rate. The colorant extract solution was added to a reactor followed by addition of an antimicrobial compound. Samples were taken at certain periods of time and they were then centrifuged to separate the flock from the mixture. The amounts of colorant compound in the solution and microbes in the flock were analyzed using a gravimetric method. The results showed that solutions of formaldehyde in water and chitosan in acetic acid could inhibit the degradation of jalawe extract. The most effective concentrations of formaldehyde and chitosan in the jalawe extract were 0.015 and 0.125%, respectively, with respect to total volume of the extract. The half-life of jalawe extract in a water based solution with the addition of formaldehyde and chitosan was 140 and 180 days respectively, while that without any addition of the antimicrobial compounds was 25 days.